1992
DOI: 10.1016/0042-6822(92)90198-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the murine cytomegalovirus genes encoding the major DNA binding protein and the ICP18.5 homolog

Abstract: In several herpesviruses the genes for the major DNA binding protein (MDBP), a putative assembly protein, the glycoprotein B (gB), and the viral DNA polymerase (pol) coliocate. In murine cytomegalovirus (MCMV), two members of this gene block, pol (Elliott, Clark, Jaquish, and Spector, 1991, Virology 185, 169-186) and gB (Rapp, Messerle, BOhler, Tannheimer, Keil, and Koszinowski, 1992, J. Virol., 66,4399-4406) have been characterized. Here the two other MCMV genes are characterized, the gene encoding the MDB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…1C). The region includes putative promoter elements and TATA and CAT boxes (CAAT), as suggested by Ross et al Furthermore, a homologue of herpes simplex virus ICP18.5 was found in the upstream region, as reported for other alphaherpesviruses (4,26,27,40).…”
Section: Mdv1 Gb Promoter Activity For Expression Of Ndv-f Cdnamentioning
confidence: 83%
“…1C). The region includes putative promoter elements and TATA and CAT boxes (CAAT), as suggested by Ross et al Furthermore, a homologue of herpes simplex virus ICP18.5 was found in the upstream region, as reported for other alphaherpesviruses (4,26,27,40).…”
Section: Mdv1 Gb Promoter Activity For Expression Of Ndv-f Cdnamentioning
confidence: 83%
“…Cytoplasmic RNA was isolated essentially as described previously (26). Glyoxal-treated RNA (5 g) was separated in 1% formaldehyde gels and transferred to nitrocellulose filters (22). To detect transcripts encompassing the UL7 ORF, the 506-bp SmaI-MluI fragment was eluted from the agarose gel after cleavage of pSub3 ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have suggested an association between SS and, mainly, hepatitis C virus (7)(8)(9) and viruses of the herpes family, including Epstein-Barr virus (EBV) (10)(11)(12)(13)(14)(15) and cytomegalovirus (CMV) (1 6,17). Murine CMV (MCMV) has homology with certain regions of human CMV (20), and MCMV infection in mice exhibits a course of infection similar to that in humans with regard to the establishment of acute and chronic infection, viral persistency and latency, and the host immune response (21,22). Murine CMV (MCMV) has homology with certain regions of human CMV (20), and MCMV infection in mice exhibits a course of infection similar to that in humans with regard to the establishment of acute and chronic infection, viral persistency and latency, and the host immune response (21,22).…”
mentioning
confidence: 99%